Accuracy of colposcopy in the Swedish screening program. (6th March 2023) - Alfonzo, Emilia; Zhang, Chenyang; Daneshpip, Forogh; Strander, Björn
Abstract: Introduction: Sensitivity and specificity of colposcopy vary greatly between studies and efficacy in clinical studies seldom corresponds with effectiveness in a real‐life setting. It is unclear whether colposcopists' experience affects assessment; studies show divergent results. The study's objective was to investigate the accuracy of colposcopies in the Swedish screening program, the variability in colposcopists' assessments and whether degree of experience affects accuracy in a routine setting. Material and methods: Cross‐sectional register study. All colposcopic assessments with a concomitant histopathological sample from women aged at least 18 years, performed between 1999 and September 2020 in Sweden. The main outcome measure was accuracy. The accuracy of colposcopic assessments was calculated as overall agreement with linked biopsies, with three outcomes: Normal vs Atypical, Normal vs Low‐Grade Atypical vs High‐Grade Atypical, and Non‐High‐Grade Atypical vs High‐Grade Atypical. A time‐trend analysis was performed. The accuracy of identifiable colposcopists related to experience was analyzed. Results: In total, 82 289 colposcopic assessments with linked biopsies were included for analysis of the outcome Normal vs Atypical; average accuracy was 63%. Overrating colposcopic findings was four times more common than underrating. No time trend in accuracy was noted during the study period. Accuracy in distinguishing High‐Grade from Non‐High‐Grade lesions was better: 76%. Among identifiable colposcopists, overall accuracy was 67%. Some had significantly better accuracy than others, but no correlation with experience was found. Conclusions: Colposcopy, including in a referral setting, has low accuracy in distinguishing Normal from Atypical. Increased experience alone does not lead to improvement. This is supported by the substantial differences in performance between colposcopists. Abstract : Colposcopy in a routine setting had low accuracy in distinguishing Normal from Atypical epithelium but improved for distinguishing High‐Grade. Increased experience alone did not improve accuracy. Overrating colposcopic findings and nonidentification of High‐Grade lesions underline the need for biopsies.